Nursing care in the handling of peripherally inserted central catheters in the neonatal ICU (Research, Society and Development, 2024)
This study addresses the advances in care with the use of technologies in newborn patients hospitalized in a Neonatal Intensive Care Unit (NICU). Neonates, who present frailties, instabilities of care on intravenous therapy, private care from the nursing team. The peripherally inserted central venous catheter (PICC) stands out as an advanced technological tool widely used in neonatology and pediatrics in patients who are in severe condition. Objective: to understand the role of nurses in the care related to the handling of peripherally inserted central catheters in the Neonatal ICU. Methodology: a research method of the Narrative Literature Review type was developed, with a descriptive nature and a qualitative approach. The Virtual Health Library (VHL) of the Ministry of Health was used as a search platform, applying the following filters: Database (LILACS and BDENF - Nursing - Brazil). Results: The following sample was obtained: 16 publications (15 articles and 2 theses) and 3 books on scientific research methodology, totaling 20 publications. Final Considerations: The literature indicated that the nursing professional has an important role in the insertion and maintenance of the PICC in the Neonatal ICU, being responsible for safe practice, aseptic technique, technical-scientific skills and knowledge, constant evaluation of the device, the professional was present in all phases of the procedure.